If you build it, will they come? Evaluation of a co‐located exercise clinic and cancer treatment centre using the RE‐AIM framework. (3rd June 2020) - Kennedy, Mary A.; Bayes, Sara; Galvão, Daniel A.; Singh, Favil; Spry, Nigel A.; Davis, Michael; Chee, Raphael; Zissiadis, Yvonne; Hart, Nicolas H.; Taaffe, Dennis R.; Newton, Robert U.
Abstract: Objective: Employ the Reach, Effectiveness, Adoption, Implementation, Maintenance framework to evaluate the effectiveness of a co‐located exercise clinic model in increasing access to exercise for people undergoing cancer treatment in a private clinic in Western Australia. Methods: This retrospective evaluation utilised a mixed‐method approach to gather feedback from key stakeholder groups involved with the exercise clinic. Questionnaires and workout summary sheets were gathered from 237 exercise clinic participants over the 50‐month evaluation period. These were supplemented by survey results from 119 patients who received cancer treatment at the facility, and semi‐structured interviews from seven radiation oncologists, eight nurses, and three accredited exercise physiologists involved with the exercise clinic. Results: The co‐located clinic demonstrated positive outcomes related to effectiveness and adoption. Participant feedback indicated satisfaction with the exercise programming (effectiveness), and clinicians were receptive to referring patients to the clinic (adoption). However, no clear implementation or maintenance plan was employed and overall reach (12%) remained suboptimal throughout the evaluation period. Conclusion: Co‐locating an exercise clinic into a treatment facility does not in itself overcome the logistical challenges of providing integrated exercise services to people during cancer treatment. To enhance its utilisation, an implementation plan needs to accompany the intervention.